Manajemen Kepala Sekolah dalam Menciptakan Budaya Organisasi Bagi Siswa di SDIT Khoiru Ummah - Kafa Sakinah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to examine the management of the principal in creating an organizational culture at SDIT Khoiru Ummah, The research approach used in this study is a qualitative approach, The findings on the management of the principal in creating an organizational culture at SDIT Khoiru Ummah are showing that the principal carries out his duties as a leader in the institution with careful planning. The principal has created a culture or